Dividend policies and managerial ability beyond financial constraints: insights from China - Dan Hou; Ziyan Yuan; Alina Taran-Bozbay; R. M. Ammar Zahid (Humanities & Social Sciences Communications)
Abstract Managerial ability plays a key role in the development and performance of a business and, implicitly, in corporate financing decisions and dividend opportunities. This study builds on the contradictory literature arguments related to dividend policies and analyses the influence of managerial ability and financial constraints on cash dividends, considering a comprehensive perspective of dividends expressed as both accounting and market measures of payout, yield, and growth in the context of the Chinese financial market. Alternative empirical estimations on a sample of 18,011 firm-year data of Chinese A-share listed companies between 2010 and 2019 indicate that managerial ability has a positive influence over cash dividend distribution, enhancing shareholders’ returns and the attractiveness of the companies on the financial market. The effect of managerial ability is challenged by the financial constraints’ conditions and state ownership. These results contribute to corporate and regulatory dividend policies, illustrating the importance of understanding the role of managerial influence on dividend decisions.